(untitled) (Research, Society and Development, 2021)
This paper aims to present and run a composite model using Genetic Algorithm (GA) and Particle Swarm (PSO), with the assistance of parallel computing methods, to optimize the electrical distribution in a power grid based on an IEEE 14-bus system. The mathematical-computational modeling allows using the objective function to analyze the cost in relation to power or voltage as independent variables, and it is the bridge for the connection between the 2 implemented algorithms. The results presented in this article demonstrate that the methodology was implemented splendidly, in addition to obtaining an excellent computational cost and complying with the physical restrictions of network security, it also achieved global solutions in its optimization.